2022
DOI: 10.3389/fneur.2022.945034
|View full text |Cite
|
Sign up to set email alerts
|

Early predictors of visual and axonal outcomes after acute optic neuritis

Abstract: BackgroundPredicting long-term visual outcomes and axonal loss following acute optic neuritis (ON) is critical for choosing treatment. Predictive models including all clinical and paraclinical measures of optic nerve dysfunction following ON are lacking.ObjectivesUsing a prospective study method, to identify 1 and 3 months predictors of 6 and 12 months visual outcome (low contrast letter acuity 2.5%) and axonal loss [retinal nerve fiber layer thickness and multifocal evoked potential (mfVEP) amplitude] followi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Not all results showed a simple increase of RD within the optic nerve, with Goodyear and colleagues [2015] ( 28 ) finding that RD within the bilateral optic nerve decreased immediately after ON and increased back to a normal level after 6 months. Interestingly, Nguyen and colleagues [2022] ( 111 ) discovered a non-linear trend where RD within the affected optic nerve was less than the unaffected nerve at baseline, whilst it yielded higher RD values 3 months after ON onset, a relationship which still persisted 12 months after onset. Goodyear and colleagues [2015] ( 28 ) also showed that the affected optic nerve showed reduced RD (along with reduced AD and MD) when compared to the unaffected nerve at onset, yet did not differ after 6-months had passed ( 109 ).…”
Section: Resultsmentioning
confidence: 99%
“…Not all results showed a simple increase of RD within the optic nerve, with Goodyear and colleagues [2015] ( 28 ) finding that RD within the bilateral optic nerve decreased immediately after ON and increased back to a normal level after 6 months. Interestingly, Nguyen and colleagues [2022] ( 111 ) discovered a non-linear trend where RD within the affected optic nerve was less than the unaffected nerve at baseline, whilst it yielded higher RD values 3 months after ON onset, a relationship which still persisted 12 months after onset. Goodyear and colleagues [2015] ( 28 ) also showed that the affected optic nerve showed reduced RD (along with reduced AD and MD) when compared to the unaffected nerve at onset, yet did not differ after 6-months had passed ( 109 ).…”
Section: Resultsmentioning
confidence: 99%
“…The strong association between the number of previous ON episodes and chiasmal MTR aligns with previous research on post-acute changes following inflammatory optic nerve lesions. 17,26 Lower MTR values are likely to reflect reduced microstructural integrity 10 which can result from both demyelination and inflammatory-related changes during the acute phase of ON, 13,27 while correlate with demyelination, remyelination and neuroaxonal loss in the longterm, [28][29][30] representing a useful marker of chronic damage and repair. 13 In our study, we observed that OC MTR values were lower in ON+ IDD patients, compared with HCs.…”
Section: Discussionmentioning
confidence: 99%
“… 17 , 26 Lower MTR values are likely to reflect reduced microstructural integrity 10 which can result from both demyelination and inflammatory-related changes during the acute phase of ON, 13 , 27 while correlate with demyelination, remyelination and neuroaxonal loss in the long-term, 28 30 representing a useful marker of chronic damage and repair. 13 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations